Recent Progress in MXenes-Based Materials for Gas Sensors and Photodetectors - Kumar, Praveen; Raza, Waseem; Suganthi, Sanjeevamuthu; Khan, Mohd Quasim; Ahmad, Khursheed; Oh, Tae Hwan (Chemosensors, 2024)
Recently, a new class of two-dimensional (2D) materials known as MXenes, such as Ti3C2Tx, have received significant attention due to their exceptional structural and physiochemical properties. MXenes are widely used in a variety of applications, including sensors, due to their excellent charge transport, high catalytic, and conducive properties, making them superior materials for sensing applications. Sensing technology has attracted significant interest from the scientific community due to its wide range of applications. In particular, gas sensing technology is essential in today’s world due to its vital role in detecting various gases. Gas sensors have an essential role in real-time environmental monitoring health assessment, and the demand for air quality monitoring is driving the gas sensor market forward. Similarly, optical sensors are a related technology that can rapidly detect toxic substances and biomaterials using optical absorption spectroscopy. MXenes are highly desirable for gas and optical sensing applications due to their abundant active sites, metallic conductivity, optical properties, customizable surface chemistry, and exceptional stability. In this review article, we compile recent advancements in the development of gas sensors and optical sensors using MXenes and their composite materials. This review article would be beneficial for researchers working on the development of MXenes-based gas sensors and optical sensors.
CRIS-Team Scopus Importer:2024-09-06
Keywords: gas sensors; MXene; optical sensors; two-dimensional material